Finland: Innovation Policy Tools under National Innovation System Crisis - Daria A. Vorobeva; Irina V. Kirichenko (Модернизация, инновация, развитие, 2017)
Purpose: the for a long time Finland’s national innovation system (NIS) had been being one of the most successful and effective in the world. But some years ago the situation changed: Finland’s NIS run into system crisis. And today Finnish government tries to work out anticrisis innovation policy. So the purpose of this article is to show up the innovation policy instruments which are able put an end to the crisis and to determine conditions of their successful use. Methods: the article is based on the national innovation systems concept and government policy-mix aimed at the NIS development. Results: the authors show up how Finnish government looks for optimal policy-mix to overcome the crisis, demonstrate in details complementary components of the relevant innovation policy, describe conditions for their success and effectiveness to consider whether they are useful in other countries. Conclusions and Relevance: to overcome the NIS crisis the Finnish government uses such instruments as strategic programs of socio-economic development with targets which can’t be achieved without adequate high technology and innovative development complemented by incentives to make business innovate actively. The conditions of such policy success are: 1) such feature of Finnish society as all stakeholders of economic development consensus on one issue: the main factor of development are innovations; 2) anticrisis stage of Finnish innovative policy is based previously accumulated knowledge and know-how.